Mutations Accounting for Congenital Fibrinogen Disorders: An Update - Richard, Maxime; Celeny, David; Neerman-Arbez, Marguerite (Seminars in Thrombosis and Hemostasis, 2022)
Fibrinogen is a complex protein that plays a key role in the blood clotting process. It is a hexamer composed of two copies of three distinct chains: Aα, Bβ, and γ encoded by three genes, FGA, FGB, and FGG, clustered on the long arm of chromosome 4. Congenital fibrinogen disorders (CFDs) are divided into qualitative deficiencies (dysfibrinogenemia, hypodysfibrinogenemia) in which the mutant fibrinogen molecule is present in the circulation and quantitative deficiencies (afibrinogenemia, hypofibrinogenemia) with no mutant molecule present in the bloodstream. Phenotypic manifestations are variable, patients may be asymptomatic, or suffer from bleeding or thrombosis. Causative mutations can occur in any of the three fibrinogen genes and can affect one or both alleles. Given the large number of studies reporting on novel causative mutations for CFDs since the review on the same topic published in 2016, we performed an extensive search of the literature and list here 120 additional mutations described in both quantitative and qualitative disorders. The visualization of causative single nucleotide variations placed on the coding sequences of FGA, FGB, and FGG reveals important structure function insight for several domains of the fibrinogen molecule.
Keywords: congenital fibrinogen disorders; mutations; afibrinogenemia; hypofibrinogenemia; dysfibrinogenemia; hypodysfibrinogenemia; bleeding; thrombosis